APLIKASI PENELUSURAN RUTE (TRACERT) LOKASI PADA PETA DIGITAL BANDA ACEH BERBASIS ANDROID - Dien Taufan L; Mizanul Ahkam; Munzir Umran (Politeknik Aceh, 2015)
Tracking route (tracert) location on a digital map of Banda Aceh can facilitate newcomers who want tofind a final destination when compared with asking others it will be a waste of time and also notnecessarily get detailed information that location. The purpose of making this application to make it easierto give location information and displays a line that will be passed. Using this application by selecting amenu that is available and choose a location that will be in the lead, and also after selecting it will go intothe destination location information. This application running on Android smartphones that can displaydigital maps and line of destination location via Google Map which is connected with a GPS smartphone.The information that is given is expected to allow users to know the location will be in the lead and isprogressing well